Biotechnology In Animal Agriculture: An Overview - Etherton, Terry D.; Bauman, Dale E.; Beattie, Craig W.; Bremel, Robert D.; Cromwell, Gary L.; Kapur, Vivek; Varner, Gary; Wheeler, Matthew B.; Wiedmann, Martin (Council for Agricultural Science and Technology (CAST), 2003)
Written by a task force of nine scientists, this issue paper summarizes existing and emerging technologies and assesses their current and potential impacts. The authors suggest that research on biotechnology in animal production is leading to breakthroughs on many fronts. Among the issues this paper addresses are uses in human and veterinary medicine; uses in animal production; vaccine development; food safety; environmental impacts; and ethical considerations of animal biotechnology.
Keywords: Biotechnology; Animal Agriculture; Vaccine Development; Environment